Table of Content - - (Arab Journal for Sciences and Research Publishing, 2025)
:Table of Content • The Role of Digital Transformation in Improving Medical Center Management Efficiency: Primary Healthcare Centers in Northern Syria as a Model Dr. Hussam Ahmad Hlaak, Dr. Ali Alhousain Aleid , TA. Attia Al-Huseyin • U.S. Interests in the Middle East and the Tools for Their Protection Mr. Tarek Jarjoura Chahine • A New Paradigm of Institutional South–South Cooperation: Arab Strategies in the South Pacific and Their Impact on Global Governance Dr. AI Hexu • Evaluation of Student Achievement Levels: A Framework for Advancing Academic Outcomes Ms. Amera Eid Alsaadi • The Expected Economic Impacts of Sudan’s Accession to the WTO: The Case of the Banking Sector 1970-2008 Dr. Abubakr Eltigani Elhag